Closing the Gap : Why Achieving Universal Health Coverage in Malawi Now Requires Targeted Investment in Underperforming and Underserved Districts - World Bank (World Bank, Washington, DC, 2021)
Most countries now agree that striving for universal health coverage (UHC) is important as it helps ensure health for all, while enhancing health security nationally, regionally and globally. Launched in 2004, the Malawi's Essential Health Package (EHP) has already gone some way towards increasing access to health services and improving health outcomes. This policy brief explores Malawi’s health system gaps and geographic variations across the three key dimensions of service availability, service readiness, and clinical knowledge of providers.